1983
DOI: 10.1139/v83-146
|View full text |Cite
|
Sign up to set email alerts
|

Triplet-state benzophenone-sensitized photoreduction of bis(acetylacetonato)copper(II): the generation and stability of copper(I) complexes

Abstract: Triplet-state benzophenone rapidly sensitized the photoreduction of Cu(acac)2 in alcohols to give polymeric Cu(acac) as black precipitates. The binary complexes of Cu(acac) of polypyridines, polysulfide, olefins, acetylenes, and carbon monoxide could be generated in solution under an inert atmosphere when a ligand was present insitu during photoreduction or added after an appropriate photoreduction was completed. Except Cu(acac)—(PPh3)2, the Cu(acac) complexes of various ligands are sensitive to air oxidation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…The yellow precipitate, which is stable to air and insoluble in any common solvent, is characteristic of polymeric alkynyl‐copper(I) complexes, possessing an infinite CuCu ladder structure with bridging RCC groups 22. Interestingly, a range of such alkynyl‐copper(I) complexes have been previously prepared by Chow and Buono‐Core through the benzophenone‐sensitized photoreduction of [Cu(acac) 2 ] in the presence of various acetylenes or, by treating a copper(I) species with acetylenes 15a. Importantly, when complex 2 is irradiated in water in the presence of RAME‐β‐CD and excess propargyl alcohol, no reduction occurs (Figure S7, the Supporting information), confirming that with 1 the reduction is driven by the benzophenone sensitizer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The yellow precipitate, which is stable to air and insoluble in any common solvent, is characteristic of polymeric alkynyl‐copper(I) complexes, possessing an infinite CuCu ladder structure with bridging RCC groups 22. Interestingly, a range of such alkynyl‐copper(I) complexes have been previously prepared by Chow and Buono‐Core through the benzophenone‐sensitized photoreduction of [Cu(acac) 2 ] in the presence of various acetylenes or, by treating a copper(I) species with acetylenes 15a. Importantly, when complex 2 is irradiated in water in the presence of RAME‐β‐CD and excess propargyl alcohol, no reduction occurs (Figure S7, the Supporting information), confirming that with 1 the reduction is driven by the benzophenone sensitizer.…”
Section: Resultsmentioning
confidence: 99%
“…The ketoprofen 2-(3-benzoylphenyl)propionic acid is a well-known commercially available non-steroidal anti-inflammatory drug containing the benzophenone chromophore and a carboxylic acid group. This choice was prompted by the work of Chow and Buono-Core who reported that certain aromatic ketones, in particular benzophenones, could sensitize the photoreduction of transition-metal complexes ML 2 such as [CuA C H T U N G T R E N N U N G (acac) 2 ] [15] and [NiA C H T U N G T R E N N U N G (acac) 2 ] (acac = acetylacetonate), [16] or [Cu(Bp) 2 ] (Bp= dihydrobis(1-pyrazolyl)borate) in hydrogendonating solvents. [17] In our preliminary account we reported the synthesis and characterization of the copper(II) complex [Cu(t-BuBz 3 tren)ketoprofenate]ketoprofenate 1 and its non-photoactivable structural analogue [Cu(t-BuBz 3 tren)acetate]acetate 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1,2] Besides the economical and practical advantages that the use of daylight as an energy source represents, exploiting light as a stimulus to activate a catalyst offers other key benefits, including potential spatial and temporal control over the catalytic event and convenient handling of stable precatalysts under ambient conditions, as well as the possibility to control the onset of the generated catalytic species by varying the irradiation parameters, typically the irradiation time, power, and excitation wavelength. [6] Inspired by the early work of Chow and Buono-Core, [14][15][16][17] we recently proposed a complementary strategy for copper-catalyst activation mediated by light. In such photocata-lytic systems continuous light irradiation is employed to generate, from an inactive copper(I) complex, a catalytically active photoexcited copper(I) species, which is able to reduce alkyl or aryl halides through single-electron-transfer processes to generate alkyl or aryl radicals.…”
Section: Introductionmentioning
confidence: 99%